2014
DOI: 10.5812/ircmj.13185
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study on Expressions of Vascular Endothelial Growth Factor, Matrix Metallopeptidase-9 and Tissue Inhibitor of Metalloproteinase-2 in Oral and Maxillofacial Squamous Cell Carcinoma

Abstract: Background:Vascular endothelial growth factor (VEGF), matrix metallopeptidase-9 (MMP-9) and tissue inhibitor of metalloproteinase-2 (TIMP-2) are potential markers of oral and maxillofacial squamous cell carcinoma (SCC).Objectives:To explore the association between expression of VEGF, MMP-9 and TIMP-2 in oral and maxillofacial SCC and clinicopathological factors.Patients and Methods:Immunohistochemical Envision method was used to analyze the expression of VEGF, MMP-9 and TIMP-2 in 54 cases of oral and maxillofa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Tumor expression of MMP‐9 was positively associated with LNM in 16 studies . Furthermore, four studies reported the association with DM, of which one found a significant positive association.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Tumor expression of MMP‐9 was positively associated with LNM in 16 studies . Furthermore, four studies reported the association with DM, of which one found a significant positive association.…”
Section: Resultsmentioning
confidence: 96%
“…Of these, 118 full‐text studies were assessed, of which 68 did not meet the inclusion criteria (Appendix 2). Therefore, 50 analytical cross‐sectional studies were included in the qualitative synthesis and 15 in the quantitative synthesis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that a prolonged MMP-2 expression promotes an increase in vasculature density, but its deficit causes vascular instability and a decrease of vascularisation(Trivedi et al, 2016). TIMP-2 can diminish the expression of VEGF, by inhibiting MMPs(Li M. et al, 2014). In the current study, a similarly tight correlation between MMP-2 and VEGF as well as between TIMP-2 and VEGF was observed, pointing out the significance of MMP-2/TIMP-2 balance for regulation of VEGF and angiogenesis.…”
mentioning
confidence: 99%